Physical Map of the Short Arm of Bread Wheat Chromosome 3D. Issue 2 (1st July 2017) - Holušová, Kateřina; Vrána, Jan; Šafář, Jan; Šimková, Hana; Balcárková, Barbora; Frenkel, Zeev; Darrier, Benoit; Paux, Etienne; Cattonaro, Federica; Berges, Helene; Letellier, Thomas; Alaux, Michael; et al.
Abstract : Bread wheat ( Triticum aestivum L.) is one of the most important crops worldwide. Although a reference genome sequence would represent a valuable resource for wheat improvement through genomics‐assisted breeding and gene cloning, its generation has long been hampered by its allohexaploidy, high repeat content, and large size. As a part of a project coordinated by the International Wheat Genome Sequencing Consortium (IWGSC), a physical map of the short arm of wheat chromosome 3D (3DS) was prepared to facilitate reference genome assembly and positional gene cloning. It comprises 869 contigs with a cumulative length of 274.5 Mbp and represents 85.5% of the estimated chromosome arm size. Eighty‐six Mbp of survey sequences from chromosome arm 3DS were assigned in silico to physical map contigs via next‐generation sequencing of bacterial artificial chromosome pools, thus providing a high‐density framework for physical map ordering along the chromosome arm. About 60% of the physical map was anchored in this single experiment. Finally, 1393 high‐confidence genes were anchored to the physical map. Comparisons of gene space of the chromosome arm 3DS with genomes of closely related species [ Brachypodium distachyon (L.) P.Beauv., rice ( Oryza sativa L.), and sorghum [ Sorghum bicolor (L.) Moench] and homeologous wheat chromosomes provided information about gene movement on the chromosome arm.